HUBUNGAN TINGKAT PENGETAHUAN DAN SIKAP KEPALA KELUARGA DENGAN KEPEMILIKAN JAMBAN SEHAT - Ni Nyoman Kartika Mila; I Ketut Ketut Aryana; NI Ketut Rusminingsih (Jurnal Kesehatan Lingkungan (JKL), 2023)
Family in the Village Seraya Tengah District Karangasem that hasn't yet healthy latrinesas many as 282 (8.6 ) KK. Researcher want know connection level knowledge and attitude head family with ownership healthy latrines. Type study use survey analytic with method Interview with approach cross sectional. Sample study as many as 97 families. Technique taking sample by simple random sampling. Data collected use sheet questionnaire , analysis statistics use test chi square. As for results level knowledge head family about healthy latrines that is own level knowledge bad namely 35 respondents , while 33 respondents and both 29 respondent. Results attitude head family about healthy latrinesthat is own attitude bad 39 respondents , moderate 36 respondents , and both 22 respondents. Results ownership healthy latrines those who have latrine 41 respondents and those who don't own  healthy latrine 56 respondents . Results test chi square that is there is connection level knowledge with ownership healthy latrines (ρ value = 0.000 0.05 ) and level connection medium (CC = 0.585 ). And there are connection attitude head family with ownership healthy latrines(ρ value = 0.000 0.05 ) and level connection medium (CC = 0.514). Expected to head family who haven't own healthy latrinesto make the simplest latrine with utilise ingredients local and latrine made  in accordance with condition healthy latrines.